The Relationship Between Psychological Empowerment and Creative Performance of Employees: Mediating Effect of Job Satisfaction in International Non-Governmental Organizations - Dina Ayoub; Dania Al-Akhras; Ghalia Na’anah; Amro Al-Madadha (European Scientific Journal, ESJ, 2018)
The aim of this study was to examine the relationship between psychological empowerment and creative performance through the mediating effect of job satisfaction in the International Non-Governmental Organization’s (INGO’s) context in Jordan. In accomplishment of this, an online questionnaire was distributed to a random representative sample of INGO’s employees working at Jesuit Refugee Service Jordan. Data were collected from 125 workers who are diverse in their gender, age, educational level, work experience and hierarchical position. Additionally, SPSS and AMO statistical software were used in order to read out the results of the filled out questionnaires. Moreover, Correlation Matrix, Multiple Regression Analysis and Mediation Analysis Process statistical tools were adopted in order to validate the proposed relationship. Sequentially, the results of the analysis validated the proposition that psychological empowerment is correlated significantly to the creative performance of employees through the mediating effect of job satisfaction.